Development of an E. coli-based norbaeocystin production platform and evaluation of behavioral effects in rats - Alexandra M. Adams; Nicholas A. Anas; Abhishek K. Sen; Jordan D. Hinegardner-Hendricks; Philip J. O’Dell; William J. Gibbons, Jr.; Jessica E. Flower; Matthew S. McMurray; J. Andrew Jones (Metabolic Engineering Communications, 2022)
Interest in the potential therapeutic efficacy of psilocybin and other psychedelic compounds has escalated significantly in recent years. To date, little is known regarding the biological activity of the psilocybin pathway intermediate, norbaeocystin, due to limitations around sourcing the phosphorylated tryptamine metabolite for in vivo testing. To address this limitation, we first developed a novel E. coli platform for the rapid and scalable production of gram-scale amounts of norbaeocystin. Through this process we compare the genetic and fermentation optimization strategies to that of a similarly constructed and previously reported psilocybin producing strain, uncovering the need for reoptimization and balancing upon even minor genetic modifications to the production host. We then perform in vivo measurements of head twitch response to both biosynthesized psilocybin and norbaeocystin using both a cell broth and water vehicle in Long-Evans rats. The data show a dose response to psilocybin while norbaeocystin does not elicit any pharmacological response, suggesting that norbaeocystin and its metabolites may not have a strong affinity for the serotonin 2A receptor. The findings presented here provide a mechanism to source norbaeocystin for future studies to evaluate its disease efficacy in animal models, both individually and in combination with psilocybin, and support the safety of cell broth as a drug delivery vehicle.